2022
DOI: 10.33050/atm.v6i1.1527
|View full text |Cite
|
Sign up to set email alerts
|

Management Information Systems on Integrated Student and Lecturer Data

Abstract: One of the most important things in universities is the development of information systems and management of integrated data, important because of the high needs and completeness of attributes in each component related to academic affairs in all universities. Primary data in academics are students and lecturers. Data management and governance are well taken care of in order to deliver information to be accurate, transparency, accountability and actual. Lecturers and students can apply the SDLC model to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 30 publications
0
23
0
2
Order By: Relevance
“…The factors that can influence people's behavior in waqf are attitudes, religious commitments, subjective norms, and the variable of using ICT technology through the community's intention to waqf. These results provide a new model in viewing people's behavior, especially the millennial generation [47].…”
Section: Research Implicationmentioning
confidence: 81%
“…The factors that can influence people's behavior in waqf are attitudes, religious commitments, subjective norms, and the variable of using ICT technology through the community's intention to waqf. These results provide a new model in viewing people's behavior, especially the millennial generation [47].…”
Section: Research Implicationmentioning
confidence: 81%
“…These transactions will be influenced by a variety of elements, such as infrastructure, regulatory framework, technological expertise, and bandwidth. The results of the cluster analysis showed that the three variables-Internet Penetration, Bitcoin Transactions per million people, and HDI-could be grouped into three significant clusters [24]. The categories from the cluster analysis are described in the sections that follow, and distributed business model concepts that are suitable for each country cluster are developed.…”
Section: The Impact Of Bitcoin On Business Models and Human Developmentmentioning
confidence: 99%
“…A few calculations and computational methodologies are utilized to guarantee that information base logging is extremely durable, sequentially requested and accessible to every other person in the organization. For sure, blockchain innovation can help the security of the created information streams both from members in the supply network and from shrewd sensors, making the supply network more solid and more secure [15].…”
Section: New Authoritative Changes With Blockchainmentioning
confidence: 99%